2021
DOI: 10.3389/fvets.2021.601794
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Semen Evaluation Using Lipidomics

Abstract: Developing a deeper understanding of biological components of sperm is essential to improving cryopreservation techniques and reproductive technologies. To fully ascertain the functional determinants of fertility, lipidomic methods have come to the forefront. Lipidomics is the study of the lipid profile (lipidome) within a cell, tissue, or organism and provides a quantitative analysis of the lipid content in that sample. Sperm cells are composed of various lipids, each with their unique contribution to the ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 129 publications
0
14
0
1
Order By: Relevance
“…In the last 20 years, development of lipidomics technologies has vastly improved by the following: i ) extensive characterization of the structures of known lipid classes and subclasses and uncovering both new classes and new molecular species of lipids (e.g., ( 4 , 74 , 134 , 135 , 136 , 137 , 138 )); ii ) sensitive quantification of lipid species at attomole to femtomole levels from a variety of biological samples (e.g., ( 132 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 )); iii ) applications for biomedical and biological studies through pathway/network analysis; iv ) biomarker development that facilitates prediction, diagnosis, and prognosis of disease states (see recent reviews for references ( 83 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 )); v ) determining the alterations of lipids in spatial distribution via mapping complex organs by MALDI imaging (see recent reviews for references ( 157 , 158 , 159 , 160 , 161 , 162 )); and vi ) advances in bioinformatics to facilitate real time data processing (e.g., ( 88 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 )).…”
Section: Current Status Of Lipidomicsmentioning
confidence: 99%
“…In the last 20 years, development of lipidomics technologies has vastly improved by the following: i ) extensive characterization of the structures of known lipid classes and subclasses and uncovering both new classes and new molecular species of lipids (e.g., ( 4 , 74 , 134 , 135 , 136 , 137 , 138 )); ii ) sensitive quantification of lipid species at attomole to femtomole levels from a variety of biological samples (e.g., ( 132 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 )); iii ) applications for biomedical and biological studies through pathway/network analysis; iv ) biomarker development that facilitates prediction, diagnosis, and prognosis of disease states (see recent reviews for references ( 83 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 )); v ) determining the alterations of lipids in spatial distribution via mapping complex organs by MALDI imaging (see recent reviews for references ( 157 , 158 , 159 , 160 , 161 , 162 )); and vi ) advances in bioinformatics to facilitate real time data processing (e.g., ( 88 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 )).…”
Section: Current Status Of Lipidomicsmentioning
confidence: 99%
“…The plasma membrane composition of sperm varies from species to species that affects the fluidity and cryoresistance or freezability of sperm (Horokhovatskyi et al, 2017; Martínez‐Páramo et al, 2012). The oxidative stress responses of sperm after cryopreservation may be associated with the lipid component and various antioxidant systems in seminal plasma and spermatozoa (Evans et al, 2021; Giraud et al, 2000; Neild et al, 2005). A previous study reported that the LPO level and the ratio of cholesterol to phospholipids in the sperm membrane of European sea bass, Dicentrarchus labrax were positively correlated with each other (Martínez‐Páramo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The fatty acid content of sperm cells has been a topic of investigation for several years [ 6 ]. Lipidomics has already been used to elucidate fatty acid groups or classes in spermatozoa from different species [ 22 ].The fatty acids lipidome of seminal fluid varied markedly between thenormozoospermia, oligoasthenoteratozoospermia, asthenozoospermia and varicocoele [ 16 ]. It has been found that the composition of saturated and unsaturated fatty acids in sperm is related to its motility, and asthenozoospermic semen samples showed lower levels of polyunsaturated fatty acids and higher levels of saturated fatty acids compared to normozoospermic samples [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipidomics is the study of the entire lipid pool within a cell, tissue, or organism, which provides a quantitative analysis of the lipid profile in that sample [ 21 ]. Lipidomics has already been used to elucidate the fatty acid groups or classes in spermatozoa from different species [ 22 ]. However, quantifying the levels or amounts of lipids has proven to be more difficult than detecting their presence.…”
Section: Introductionmentioning
confidence: 99%